Histadruth. General Federation of Jewish Labour in Palestine : facts and figures submitted to the Delegates of the World Trade Union. - Histadruth. General Federation of Jewish Labour in Palestine (London, 1945)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: joodse arbeidersbeweging; vakbonden; Palestina